The Effect of Digital Marketing and Customer Experience on Customer Loyalty at Maju Bersama Ringroad - Jenniefer Killiam; Dedy Lazuardi (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2024)
To increase company sales can be done in various ways, one of which is by maintaining customer loyalty. In this digital era, maintaining customer loyalty is no longer hindered by distance and time, only with social media alone customers can be contacted. Customer loyalty can also be maintained by improving the customer experience by providing certain offers and bonuses. This research uses quantitative data with the population being customers at Maju Bersama Ringroad. The sample was obtained using the Hair et al. formula so that a sample of 120 respondents was obtained. The results showed that digital marketing and customer experience partially affect customer loyalty at Maju Bersama Ringroad. Then simultaneously, digital marketing and customer experience partially affect customer loyalty at Maju Bersama Ringroad with a coefficient of determination of 58.9%.